Pemahaman, Kesadaran Wajib Pajak, Kualitas Pelayanan Fiskus, dan Ketegasan Sanksi Terhadap Kepatuhan Wajib Pajak - Vanessa Dana, Desak Made Indy; Jati, I Ketut (E-Jurnal Akuntansi; Vol 34 No 10 (2024)DO - 10.24843/EJA.2024.v34.i10.p20, 2024)
This study aims to offer empirical evidence regarding the influence of understanding, awareness of taxpayers, quality of tax authorities' services, and firmness of witnesses on taxpayer compliance. A total of 68,041 individual taxpayers registered at KPP Pratama Singaraja became the study population. A sample of 100 respondents was selected using the slovin formula. Accidental sampling is the sampling technique used. Multiple linear regression is the analytical method used. According to research findings, understanding, awareness of taxpayers, quality of tax services, and strictness of sanctions all have a positive impact on individual taxpayer reporting compliance registered at KPP Pratama Singaraja.